2020
DOI: 10.1108/gkmc-09-2019-0119
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of education and continuing professional development (CPD) of academic libraries workforce in Botswana

Abstract: Purpose The purpose of this study is to assess the current level of education qualifications of the workforce working in academic libraries in Botswana. The study also aims to determine the current and required level of continuing professional development (CPD) of librarians working in academic libraries in Botswana. Design/methodology/approach The study adopted positivist research paradigm and quantitative research design using a structured questionnaire to collect data, where survey questions were develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…They were found wanting in attending formal conferences, workshops and training events, and should be supported to do so. Oladokun et al’s (2021) findings reveal that while 57 (49.1%) respondents claimed they had attended conferences, only 27 (23.3%) – less than half – had published or presented a paper. Table 8 in the present study also shows a low mean of 1.89 with regard to ‘Research and publishing in the field of study’.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…They were found wanting in attending formal conferences, workshops and training events, and should be supported to do so. Oladokun et al’s (2021) findings reveal that while 57 (49.1%) respondents claimed they had attended conferences, only 27 (23.3%) – less than half – had published or presented a paper. Table 8 in the present study also shows a low mean of 1.89 with regard to ‘Research and publishing in the field of study’.…”
Section: Discussionmentioning
confidence: 93%
“…Integrating the elements and benefits of both quantitative research and qualitative research, George (2021) states that mixed methods can assist in gaining a more complete picture than a stand-alone quantitative or qualitative study. This study is a continuation of Oladokun et al’s (2021) work, which used only quantitative data. The current study adopted both a quantitative and a qualitative approach.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…And from an academic perspective, it emerged as a dependable, robust and systematic alternative educational option. Oladokun et al (2021) observed that having education, training or professional certification did not guarantee employment; it is also crucial to be able to function well at work.…”
Section: Continued Intentions To Pursue E-learningmentioning
confidence: 99%